Coxiella burnetiias a useful tool to investigate bacteria-friendly host cell compartments - Pechstein, Julian; Schulze-Luehrmann, Jan; Lührmann, Anja (International Journal of Medical Microbiology, 2017)
Coxiella burnetii is an obligate intracellular and airborne pathogen which can cause the zoonotic disease Q fever. After inhalation of contaminated aerosols alveolar macrophages are taking up C. burnetii into a phagosome. This phagosome matures to a very large vacuole called the C. burnetii-containing vacuole (CCV). Host endogenous and bacterial driven processes lead to the biogenesis of this unusual compartment, which resembles partially a phagolysosome. However, there are several important differences to the classical phagolysosome, which are crucial for the ability of C. burnetii to replicate intracellularly and depend on a functional type IV secretion system (T4SS). The T4SS delivers effector proteins into the host cell cytoplasm to redirect intracellular processes, leading to the establishment of a microenvironment allowing bacterial replication. This article summarizes the current knowledge of the microenvironment permissive for C. burnetii replication.
EVALuna2:7729

Modulation of host cell apoptotic pathways by intracellular pathogens - Friedrich, Anja; Pechstein, Julian; Berens, Christian; Lührmann, Anja (Current Opinion in Microbiology, 2017)
Nearly all steps of the host cell apoptotic cascade can be subverted by intracellular microorganisms. Some pathogens modulate early steps and interfere with sensing of extracellular signals, cellular stress or signal transduction; others target Bcl-2 proteins, caspases, or inhibitor of apoptosis proteins (IAPs). In many cases the exact molecular mechanisms leading to interference with the host cell apoptotic cascade are still unknown. However, there are some examples where bacterial factors that modulate host cell death have been identified. In this review we will summarize recent findings on how intracellular pathogens or their secreted proteins alter the intrinsic and/or extrinsic host cell apoptotic pathways.
EVALuna2:7732

The Coxiella burnetii T4SS Effector AnkF Is Important for Intracellular Replication - Pechstein, Julian; Schulze-Luehrmann, Jan; Bisle, Stephanie; Cantet, Franck; Beare, Paul A.; Olke, Martha; Bonazzi, Matteo; Berens, Christian; Lührmann, Anja (Frontiers in Cellular and Infection Microbiology, 2020)
Coxiella burnetii is an obligate intracellular pathogen and the causative agent of the zoonotic disease Q fever. Following uptake by alveolar macrophages, the pathogen replicates in an acidic phagolysosomal vacuole, the C. burnetii-containing vacuole (CCV). Effector proteins translocated into the host cell by the type IV secretion system (T4SS) are important for the establishment of the CCV. Here we focus on the effector protein AnkF and its role in establishing the CCV. The C. burnetii AnkF knock out mutant invades host cells as efficiently as wild-type C. burnetii, but this mutant is hampered in its ability to replicate intracellularly, indicating that AnkF might be involved in the development of a replicative CCV. To unravel the underlying reason(s), we searched for AnkF interactors in host cells and identified vimentin through a yeast two-hybrid approach. While AnkF does not alter vimentin expression at the mRNA or protein levels, the presence of AnkF results in structural reorganization and vesicular co-localization with recombinant vimentin. Ectopically expressed AnkF partially accumulates around the established CCV and endogenous vimentin is recruited to the CCV in a time-dependent manner, suggesting that AnkF might attract vimentin to the CCV. However, knocking-down endogenous vimentin does not affect intracellular replication of C. burnetii. Other cytoskeletal components are recruited to the CCV and might compensate for the lack of vimentin. Taken together, AnkF is essential for the establishment of the replicative CCV, however, its mode of action is still elusive.
CRIS-Team WoS Importer:2020-12-11